Real‐world evidence for subcutaneous infliximab (CT‐P13 SC) treatment in patients with ankylosing spondylitis during the coronavirus disease (COVID‐19) pandemic: A case series. Issue 1 (13th January 2022) - Vijayan, Sooraj; Hwangbo, Kyungmin; Barkham, Nick
Abstract: The COVID‐19 pandemic emphasized the utility of subcutaneous (SC) biologics for pressured healthcare systems. The first SC form of infliximab, CT‐P13 SC, provided safe and effective treatment for ankylosing spondylitis in our case series, with increased convenience relative to intravenous treatment benefitting patients both during the pandemic and beyond.